The science of cheese - Tunick, Michael (Oxford University Press, 2013)
In an engaging tour of the science and history of cheese, Michael Tunick explores the art of cheese making, the science that lies underneath the deliciousness, and the history behind how humanity came up with one of its most varied and versatile of foods. Dr. Tunick spends his everyday deep within the halls of the science of cheese, as a researcher who creates new dairy products, primarily, cheeses. He takes us from the very beginning, some 8000 years ago in the Fertile Crescent, and shows us the accidental discovery of cheese when milk separated into curds and whey. This stroke of luck would.